Pendidikan Kesehatan Self Care Activity pada Pasien Diabetes Mellitus Tipe 2 - Willady Rasyid; Hidayatul Rahmi; Deski, Febby Irianti (Universitas Alifah Padang, 2024)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by chronic hyperglycemia due to impaired insulin secretion, decreased insulin action, or both, which can cause long-term damage to various organs. DM patients who are not managed properly are at risk of experiencing macro and micro complications, which increase morbidity. Self-care activity is an important strategy in controlling blood glucose levels and preventing DM complications. There are five important points in DM management: diet, exercise, pharmacological therapy, blood sugar monitoring, and foot care. Kuranji Health Center faces an increase in DM cases every year and a lack of patient knowledge about type 2 DM and self-care activity. This community service (PKM) aims to improve knowledge and management of self-care activity in an effort to reduce blood glucose levels and prevent complications in type 2 DM patients. The program is implemented by providing self-care activity health education. The location of the PKM activity is at the Kuranji Padang Health Center. This activity began with the provision of health education about type 2 DM and self-care activity. This community service activity was attended by 30 participants. Before being given PKM, the patient's knowledge was poor as many as 25 people (83.3%) and good knowledge as many as 5 people (16.7%) then after being given PKM, the patient's knowledge became good as many as 29 people (96.7%).